The Role of Robotics-Driven Productivity, Profit, and Employee Satisfaction in Enhancing Sustainability in the Beverage Industry - Jimoh Adams Lukman; Zi Jian Oh; Muhammad Azim Akmal bin Johani; Muhammad Alimi bin Mohd Tarmizi; Muhammad Afiq Hakimie bin Ahmad Sobri; Muhammad Amar Basyir bin Sulaiman; Suryo Wirawan; Dhymas Pramana Wicaksana; Mikita Trusevich; Daisy Mui Hung Kee (AIBPM Publisher, 2024)
This research examines the perceptions of individuals from diverse backgrounds regarding the role of robotics in the Coca-Cola industry, focusing on productivity, profitability, and employee satisfaction. The objective was to evaluate how robotics impacts organizational efficiency and sustainability in beverage manufacturing, especially Coca-Cola. A quantitative methodology was employed, utilizing a Google Form questionnaire distributed to 50 respondents from Malaysia, Indonesia, India, and Belarus. The survey assessed the perceived productivity, profitability, and satisfaction related to robotic integration in Coca-Cola's operations. Results indicated that respondents rated the productivity of robotics positively, with a mean score of 3.84, suggesting a strong perception of automation’s efficiency. Profitability was similarly viewed favorably, with a mean of 3.86, indicating that robotics contributes to organizational profitability. Employee satisfaction with robotics had a slightly lower mean score of 3.82, reflecting a neutral to positive outlook. In conclusion, robotics significantly enhances productivity and profitability in the beverage industry, while employee satisfaction, though important, has a secondary impact on sustainability outcomes.